Curcumin boosts DHA in the brain: implications for the prevention of anxiety disorders - Wu, Aiguo (Biochim Biophys Acta, 2014)
Dietary deficiency of docosahexaenoic acid (C22: 6n-3; DHA) is linked to the neuropathology of several cognitive disorders, including anxiety. DHA, which is essential for brain development and protection, is primarily obtained through the diet or synthesized from dietary precursors, however the conversion efficiency is low. Curcumin (diferuloylmethane), which is a principal component of the spice turmeric, complements the action of DHA in the brain, and this study was performed to determine molecular mechanisms involved. We report that curcumin enhances the synthesis of DHA from its precursor, α-linolenic acid (C18: 3n-3; ALA) and elevates levels of enzymes involved in the synthesis of DHA such as FADS2 and elongase 2 in both liver and brain tissue. Furthermore, in vivo treatment with curcumin and ALA reduced anxiety-like behavior in rodents. Taken together, these data suggest that curcumin enhances DHA synthesis, resulting in elevated brain DHA content. These findings have important implications for human health and the prevention of cognitive disease, particularly for populations eating a plant-based diet or who do not consume fish, a primary source of DHA, since DHA is essential for brain function and its deficiency is implicated in many types of neurological disorders.